2018
DOI: 10.1038/s41598-018-32034-9
|View full text |Cite
|
Sign up to set email alerts
|

Blocking HIF signaling via novel inhibitors of CA9 and APE1/Ref-1 dramatically affects pancreatic cancer cell survival

Abstract: Pancreatic ductal adenocarcinoma (PDAC) has reactive stroma that promotes tumor signaling, fibrosis, inflammation, and hypoxia, which activates HIF-1α to increase tumor cell metastasis and therapeutic resistance. Carbonic anhydrase IX (CA9) stabilizes intracellular pH following induction by HIF-1α. Redox effector factor-1 (APE1/Ref-1) is a multifunctional protein with redox signaling activity that converts certain oxidized transcription factors to a reduced state, enabling them to upregulate tumor-promoting ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 58 publications
1
54
0
Order By: Relevance
“…These 11 gene sets were then subjected to survival analysis for a better understanding of their role according to a clinical perspective. LIHC, LUAD and PAAD networks, which were composed of bad prognostic genes in high percentages, confirmed previous studies on the important role of APE1 in these cancers [52][53][54][55][57][58][59][60][61][62][63][64][65] . Kaplan-Meier estimation was used to calculate survival probability associated with these genes; the ones having significantly lower survival prognosis (p < 0.05) were used to create cancer-specific PPI subnetworks ( Fig.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These 11 gene sets were then subjected to survival analysis for a better understanding of their role according to a clinical perspective. LIHC, LUAD and PAAD networks, which were composed of bad prognostic genes in high percentages, confirmed previous studies on the important role of APE1 in these cancers [52][53][54][55][57][58][59][60][61][62][63][64][65] . Kaplan-Meier estimation was used to calculate survival probability associated with these genes; the ones having significantly lower survival prognosis (p < 0.05) were used to create cancer-specific PPI subnetworks ( Fig.…”
Section: Discussionsupporting
confidence: 88%
“…In order to focus our attention on the most relevant cancer types, we based our bioinformatic analysis on the eleven datasets having the highest number of bad prognostic genes. Among those, we were interested in particular in liver (LIHC) [52][53][54][55][56] , lung (LUAD) [57][58][59][60] and pancreatic (PAAD) [61][62][63][64][65] cancer datasets, as the essential role of APE1 in the tumorigenic processes of these cancer types is already well established. Notably, the LUAD dataset was the third having the highest number of bad prognostic genes (n = 153).…”
Section: Upstream Regulators Analysismentioning
confidence: 99%
“…On the one hand, APE1 functions as an endonuclease involved in DNA base excision repair, it is closely related to tumor cell proliferation; on the other hand, it regulates the activity of redox-sensitive transcription factors (12). Many studies showed APE1 over-expression in a variety of tumors (13)(14)(15). Some scholars used enzyme-linked immunosorbent assay to detect serum APE1 in patients suffering from bladder cancer without chemotherapy or radiotherapy (51 cases) and in a non-tumor control group (55 cases).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a combination treatment with APE1/Ref-1 inhibitor E3330 and CAIX inhibitor SLC-0111 (Clinical Trial NCT02215850) was shown to reduce proliferation and size of three-dimensional spheroids derived from PDAC patients [64]. In line with these findings, the application of novel analogues of both APE1/Ref-1 and CAIX inhibitors (namely APX2009, APX2014, and FC12-531A) with improved potency significantly affected pancreatic cancer cell survival [65].…”
Section: Signaling Pathways Activated In Pancreatic Tumors and Their mentioning
confidence: 80%
“…SLC-0111-mediated CAIX inhibition has proven to be effective in patient-derived 2D and 3D PDAC cell cultures [64,65], followed by an SLC-0111 safety study (NCT02215850) in advanced solid tumors. Currently, a Phase 1/2 clinical trial (NCT03450018) uses the selective, small molecule inhibitor SLC-0111 in CAIX-positive patients diagnosed with metastatic PDAC.…”
Section: Caixmentioning
confidence: 99%